Strategi Marketing Public Relations Daily Folks Coffee melalui Media Sosial Instagram - Alya Khairunnisa; Dadi Ahmadi (UNISBA Press, 2022)
Abstract. Daily Folks Coffee is an MSME engaged in the Food and Beverage (F&B) sector. Before the pandemic, in carrying out its Marketing Public Relations Strategy, Daily Folks Coffee always participated in offline events to spread its wings. At the end of 2019, the Covid-19 pandemic occurred which made all MSMEs have to replane a new marketing Public Relations Strategy and follow the protocols determined by the government. This research is entitled “Daily Folks Coffee Marketing Public Relations Strategy Through Instagram Social Media”. The Focus of this research is how the Marketing Public Relations Strategy of Daily Folks Coffee in Marketing in the Pandemic Period through Instagram Sosial Media. The purpose of this research is to find out how the method used by Marketing Public Relations Daily Folks Coffee to still be able to reach the masses despite the pandemic, and what the Marketing Public Relations do to still be able to market Daily Folks Coffee products with very limited when face a pandemic. This study uses a qualitative method with a descriptive study approach. And by using the Public Relations Strategy Three Ways Strategy (Push Strategy, Pull Strategy, and Pass Strategy) according to Thomas L Harris. The subjects in this study were part of the Daily Folks Coffee itself. Data Collection techniques in this study are using interviews, observation, and gathering information and documentation to strengthen research data. The result of this study asses how the marketing public relations process for Daily Folks Coffee can still maintain its existence in the face of a crisis or pandemic that is happening all over the world. In attracting consumers, Daily Folks Coffee uses Instagram social media and makes bundling packages as well as offers interesting promos and content. In addition, Daily Folks Coffe works with its barista’s to encourage product sales. Daily Folks Coffee also provides several free products to influencers or well-known celebrities engaged in social media, especially Instagram to encourage sales of Daily Folks Coffee products. Abstrak. Daily Folks Coffee adalah sebuah UMKM yang bergerak di bidang Food and Beverage (F&B). Sebelum terjadinya pandemic, dalam melakukan Strategi Marketing Public Relations nya, Daily Folks Coffee selalu mengikuti event-event offline untuk melebarkan sayapnya. Pada akhir 2019, terjadi pandemic Covid-19 yang membuat seluruh UMKM harus merencanakan ulang Strategi Marketing Public Relations yang baru dan mengikuti protokol yang telah ditentukan oleh pemerintah. Penelitian ini berjudul “Strategi Marketing Public Relations Daily Folks Coffee Melalui Media Sosial Instagram”. Fokus penelitian ini adalah Bagaimana Strategi Marketing Public Relations Daily Folks Coffee Dalam Pemasaran di Masa Pandemi melalui Media Sosial Instagram. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana metode yang dilakukan Marketing Public Relations Daily Folks Coffee untuk tetap bisa menjangkau massa-nya meskipun adanya pandemi, dan apa yang dilakukan pihak Marketing Public Relations-nya untuk tetap dapat memasarkan produk Daily Folks Coffee dengan sangat terbatas ketika menghadapi pandemi. Penelitian ini menggunakan Metode Kualitatif dengan Pendekatan Studi Deskriptif. Dan dengan menggunakan Strategi Public Relations Three Ways Strategy (Push strategy, Pull strategy, dan Pass Strategy) menurut Thomas L Harris. Subjek dalam penelitian ini adalah orang-orang yang menjadi bagian dari Daily Folks Coffee ini sendiri. Teknik pengumpulan data dalam penelitian ini yaitu menggunakan wawancara, observasi, dan pengumpulan informasi dan dokumentasi untuk memperkuat data penelitian. Hasil dari penelitian ini menilai bagaimana proses Marketing Public Relations Daily Folks Coffee yang tetap bisa mempertahankan eksistensinya dengan kondisi krisis atau pandemi yang terjadi di seluruh dunia ini. Dalam menarik konsumennya, Daily Folks Coffee menggunakan media sosial Instagram dan membuat paketan-paketan bundling serta promo-promo dan konten menarik yang ditawarkan. Selain itu juga, Daily Folks Coffee ini bergerak bersama barista-baristanya untuk mendorong penjualan produk. Daily Folks Coffee juga memberikan beberapa free product kepada influencer atau selebgram ternama yang bergerak dibidang sosial media, khususnya Instagram untuk mendorong penjualan produk Daily Folks Coffee.